La convivencia escolar a través de la danza - Cocunubo Valbuena, Oscar Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article had as a principle objective to strengthen trough dance the coe- xistence between the students of the fifth grade, considering that their range of age goes from 9 to 11 years old, from the school called Andes located in Bogotá. Therefore we had to look for the experience´s level of coexistence between the students through a screening test, that made possible the de- sign of a program of activities that we evaluated by the means of another test. The approximation used was mixed and the investigation was carried out through Action Research. It was concluded that dance, besides having a great educational and pedagogical impact on the students, it´s an activity of a great deal of importance from the social and cultural standpoint, being a perfect conduct of ideas.